ANALISIS DISTRIBUSI DAN PREDIKSI HASIL TANGKAPAN JARING ARAD MENGGUNAKAN ALGORITMA BACKPROPAGATION NEURAL NETWORK - Alya Dina Wilujeung, - (2023)
Fish production in Muara Gading Mas decreased with the ban on the use of Trawls. However, currently fish production shows an increase along with the development of modified fishing gear from the trawl, namely arad nets. However, information on the distribution pattern of catches ranging from fish on land in TPI to consumers is not yet available, besides that there has never been a prediction of catches to support the distribution supply. The purpose of the study was to determine the distribution pattern of the arad net catch and predict the catch. The method used is a case study with implementation in November 2021 to March 2022. To find out the distribution pattern of the analysis applied is Supply Chain while prediction uses Conjugate Gradient analysis on the Back Propagation Neural Network in obtaining the best value. The results of the supply chain analysis were obtained that TPI Muara Gading Mas has been able to provide supplies for the surrounding areas by 94% but for out-of-town destinations by 6%. Based on the test results, the parameters of the BPNN algorithm, learning rate of 0.1, error tolerance of 0.01 and epoch of 50 have obtained good accuracy with a mean square error (MSE) value of 1.2446 x 10-6. The results showed that the BPNN algorithm can be used as an alternative forecasting method. Keywords: Arad, Distribution, Fish, TPI Muara Gading Mas, Forecasting